1971
DOI: 10.1677/joe.0.0490029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroidectomy on the Development of Nephrocalcinosis and Calcium, Phosphorus and Magnesium Balance in Rats

Abstract: Rats of different strains raised on a semipurified casein\p=m-\sugar diet, develop a nephrocalcinosis in which deposits composed principally of calcium and phosphorus accumulate at the corticomedullary junction of the kidney. To determine whether the development of this nephrocalcinosis was in any way related to the activity of the parathyroid glands, female weanling 21-day-old rats were parathyroidectomized (PTX) or sham\x=req-\ operated and fed the semipurified diet for 3 weeks. Absorption, retention and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In our study, oestrogens in OCA may have inhibited bone resorption to a sufficient degree to lower serum calcium concentration, thus evoking a compensatory increase in FTH secretion. A rise in circulating PTH would, in effect, maintain a normal serum calcium concentration at a lower level of bone resorption andahigher level of tubular calcium reabsorption, since the response of bone to PTH is blunted by oestrogens while the response of the kidney is unaltered (Heaney, 1975).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, oestrogens in OCA may have inhibited bone resorption to a sufficient degree to lower serum calcium concentration, thus evoking a compensatory increase in FTH secretion. A rise in circulating PTH would, in effect, maintain a normal serum calcium concentration at a lower level of bone resorption andahigher level of tubular calcium reabsorption, since the response of bone to PTH is blunted by oestrogens while the response of the kidney is unaltered (Heaney, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium and potassium were measured with an IL Model 143 flame photometer, with lithium as internal standard. Calcium and magnesium were determined by atomic absorption spectrophotometry (Goulding &, Malthus, 1971) and creatinine by a standard alkaline picrate procedure (Wootton, 1964). Data were processed on a Burroughs B6700 computer and statistical comparisons between mean values of different groups made by Student's t test.…”
Section: Subjects a N D Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies have shown decreased [105] or in creased [107] bone magnesium content in parathyroidectomized magnesium-deficient rats, increased femoral magnesium content in parathyroidectomized rats and increased bone magnesium in uremic rats undergoing parathyroidectomy [108][109][110]. In vitro models focusing upon PTH have also been studied [111][112][113].…”
Section: Parathyroid Hormone and Magnesiummentioning
confidence: 99%